DISEASE DIAGNOSIS EXPERT SYSTEM ON FRESHWATER AQUACULTURE FISH USING FORWARD CHAINING ANDROID BASED - Ardhika Praseda Ageng Putra; Aristoteles Aristoteles; Rara Diantari (Jurnal Komputasi, 2016)
Fish disease is undesirable for fish farmers, because it can cause low productivity and high mortality aquaculture. Lack of information on disease prevention methods small number of experts causing many farmers suffered losses. Therefore, an expert system is needed to help diagnose the disease in fish. This system aims to help cultivators on resolve fish disease problem. In this research, expert system based on android was built using Java program language as database, Forward chaining was used. This method used to determine which roles will be executed, then that rule is executed, the process was repeated until we got the result. This system can diagnose 35 diseases from 8 species of fish. The data testing result used Equivalence Partitioning, showed that management rules system can run based on its function and system can diagnose the disease well. On the other based on questionnaire data, this application is an user friendly application (with average value of 4,29 / excellent). Keywords: Forward Chaining, Freshwater Aquaculture Fish Disease, Expert Systems, Android